Comparison the Results of Humerus Shaft Fractures Treated by Functional Bracing versus Dynamic Compression Plate - Ariful Islam, Syed; Kumar Das, Chandan; Abedin, Md Jainal; Alam, Md Mahabub; Chakrobortty, Partho Protim; Barua, Shaon (Medicine Today, 2024)
Introduction with Objective: To compare the results of humerus shaft fractures treated by functional bracing and dynamic compression plate. Materials and Methods: This experimental study was carried out at the Department of Orthopedic Surgery at Chittagong Medical College Hospital, Chattogram from August 2019 to July 2021. All adult patients of closed diaphyseal fracture of humerus attending the Orthopaedics department, Chittagong Medical College Hospital during study period were the study population. Purposive sampling was done according to availability of the patients. Cases were divided in two groups; group A (dynamic compression plate) and group B (functional bracing). All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science. The results were expressed as percentage and mean ± SD and p<0.05 was considered as the level of significant. Result: Average mean ± SD age was 40.22 ± 12.451 (range: 19-65) years. The mean age was 37.24 ± 10.686 in plating group and 43.20 ± 13.559 in bracing group. Out of 50 patients, 30 (60%) were male and 20 (40%) were female. Male was predominant in both groups (P=0.564). Regarding time taken for radiological union, average mean ± SD time was 15.32 ± 2.613 (range: 12-22) weeks. The mean time for radiological union was 14.91 ± 2.712 weeks in plating group and 15.76 ± 2.488 weeks in bracing group. Regarding ROM of shoulder & elbow, there was statistically nonsignificant difference found between the groups except shoulder flexion (P= 0.031s), abduction(P=0.025s) & extension(P=0.041s) more on plating group. QUICK-DASH score at 3 month shows highly significant difference between the study groups (p=0.001). At 6 and 12 month significant difference was found between the groups. Out of 44 patients at 12 months follow-up, 19 (43.2%) patient’s functional outcome was excellent and 10 (22.7%) patient’s functional outcome was good. Statistically significant difference was found between the groups (p=0.022). Conclusion: This study observed that functional outcome was relatively better in patients treated by dynamic compression plate in adult diaphyseal fracture of humerus. Medicine Today 2024, Vol.36 (2): 82-86